2011
DOI: 10.1128/aem.00314-11
|View full text |Cite
|
Sign up to set email alerts
|

Methylotrophy in a Lake: from Metagenomics to Single-Organism Physiology

Abstract: This review provides a brief summary of ongoing studies in Lake Washington (Seattle, WA) directed at an understanding of the content and activities of microbial communities involved in methylotrophy. One of the findings from culture-independent approaches, including functional metagenomics, is the prominent presence of Methylotenera species in the site and their inferred activity in C 1 metabolism, highlighting the local environmental importance of this group. Comparative analyses of individual genomes of Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 52 publications
1
50
0
Order By: Relevance
“…Of late, though, the NMG pathway is going through a phase of rediscovery, in light of its importance in several environmental regimes (7,51,52). While various studies with different model systems FIG 6 (A) Red, blue, and green arrows represent the deletion of fae, fae2, and fae3, respectively, in the genomic background from which the arrow originates.…”
Section: Discussionmentioning
confidence: 99%
“…Of late, though, the NMG pathway is going through a phase of rediscovery, in light of its importance in several environmental regimes (7,51,52). While various studies with different model systems FIG 6 (A) Red, blue, and green arrows represent the deletion of fae, fae2, and fae3, respectively, in the genomic background from which the arrow originates.…”
Section: Discussionmentioning
confidence: 99%
“…We also mutated a gene predicted to encode a nitric oxide dioxygenase (Nod; mmol_1063) and each of two xoxF genes (mmol_1770 and mmol_2048) that encode homologs of the large subunit of methanol dehydrogenase (11,14,19,20). In addition, a double mutant lacking both XoxF proteins was generated.…”
Section: Mutant Growth Phenotypesmentioning
confidence: 99%
“…Methylotenera species represent a recently described novel genus within the family Methylophilaceae (11). Apart from genomic divergence (12), one of the main properties that distinguishes the described species of Methylotenera from species representing three other genera within this family (Methylophilus, Methylobacillus, and Methylovorus) is extremely poor growth on methanol and the lack of genes for the classic (MxaFI) methanol dehydrogenase (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have provided evidence for the physiological role of a second type of PQQ-dependent MDH, XoxF, which has ϳ50% amino acid identity to MxaF from MxaFI-type MDHs (17). Metagenomic and environmental proteomics studies have demonstrated that xoxF is more widespread than mxaF in environmental samples (18)(19)(20)(21). Phylogenetic analysis of putative PQQ-containing MDHs has shown that XoxF-type MDHs are genetically diverse with at least five distinct clades, and it has been suggested that MxaFI-type MDHs represent a minor fraction of these MDHs (8,22).…”
mentioning
confidence: 99%